2020
DOI: 10.1093/mnras/staa2245
|View full text |Cite
|
Sign up to set email alerts
|

Pixel level decorrelation in service of the Spitzer microlens parallax survey

Abstract: Microlens parallax measurements combining space-based and ground-based observatories can be used to study planetary demographics. In recent years, the Spitzer Space Telescope was used as a microlens parallax satellite. Meanwhile, Spitzer IRAC has been employed to study short-period exoplanets and their atmospheres. As these investigations require exquisite photometry, they motivated the development of numerous self-calibration techniques now widely used in the exoplanet atmosphere community. Specifically, Pixe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
2
5
0
Order By: Relevance
“…Systematics at the level of ∼1 flux unit have been seen in several events (e.g., Poleski et al 2016;Dang et al 2020;Gould et al 2020;Hirao et al 2020) and are confirmed in this case. The potential impact of systematics will be most pronounced in events for which the overall flux change is small (e.g., for Δf Spz  10 flux units).…”
Section: Potential Impact Of Systematicssupporting
confidence: 75%
“…Systematics at the level of ∼1 flux unit have been seen in several events (e.g., Poleski et al 2016;Dang et al 2020;Gould et al 2020;Hirao et al 2020) and are confirmed in this case. The potential impact of systematics will be most pronounced in events for which the overall flux change is small (e.g., for Δf Spz  10 flux units).…”
Section: Potential Impact Of Systematicssupporting
confidence: 75%
“…Systematics at the level of ∼ 1 flux unit have been seen in several events (e.g., Poleski et al 2016;Dang et al 2020;Gould et al 2020;Hirao et al 2020) and are confirmed in this case. The potential impact of systematics will be most pronounced in events for which the overall flux change is small (e.g., for ∆f Spz 10 flux units).…”
Section: Potential Impact Of Systematicssupporting
confidence: 71%
“…Unfortunately, the orbital motion of the Earth allows π E to be determined for only a relatively small subset of events such as the ones that have very long durations (e.g., Gaudi et al 2008;Bennett et al 2010b), long duration events with bright source stars (e.g., Muraki et al 2011), and events with special lens geometries (e.g., Sumi et al 2016). The microlensing parallax program using the Spitzer space telescope at ∼1 au from Earth has recently expanded the number of events with microlensing parallax measurements (Udalski et al 2015;Street et al 2016), but recent studies indicate that systematic errors in the Spitzer photometry can affect some of the Spitzer π E measurements (Dang et al 2020;Gould et al 2020;.…”
Section: Introductionmentioning
confidence: 99%